Використання класифікації за Pipkin у визначенні тактики лікування переломів головки стегнової кістки - Головаха, Максим Леонідович; Орлянський, В.; Браунштайнер, Т.; Лісунов, Михайло Сергійович; Перцов, Володимир Іванович; Golovakha, M. L.; Orljanskі, W.; Braunsteiner, T.; Lisunov, M. S.; Pertsov, V. I. (My University, 2024)
Femoral head fractures are a rare injury with limited information in the literature. Recent studies have been based on small case series, indicating that the incidence of fractures in hip dislocation varies from 7 to 18 %. Fractures of the femoral head are classified according to Pipkin. Treatment is often accompanied by significant complications, and the choice of the optimal treatment method remains a matter of debate. The choice of treatment tactics affects the duration of treatment and functional outcome. The article presents the results of treatment of patients whose treatment tactics were based on the Pipkin classification. Objective. To substantiate the use of the Pipkin classification of femoral head fractures in the selection of treatment and diagnostic tactics. Methods. The study was performed by evaluating the results of treatment in 44 patients. The Pipkin classification was used to determine the treatment tactics. The results were evaluated according to the HHS scale. The results were statistically analysed by comparing the median scores for different groups using the Mann-Whitney U test. Results. The worst prognosis was for patients with Pipkin III and Pipkin IV fractures. HHS scores for patients with complicated outcomes are worse than for patients with uncomplicated outcomes. Treatment outcomes for Pipkin type III fractures are statistically significantly lower than for other types. Conclusions. Pipkin fractures are a rare and severe injury that can cause significant limb dysfunction with proper treatment. Treatment of Pipkin type I and type II includes immediate reduction of the dislocation and conservative treatment in case of satisfactory fragmentation or open reduction with metal osteosynthesis for displaced fractures; for type III and IV, open reduction and osteosynthesis are possible for young patients, and primary arthroplasty is recommended for patients over 60 years of age or with concomitant metabolic diseases. Key words. Fracture of the femoral head, dislocation of the hip, hip joint, osteosynthesis, endoprosthetics. Переломи головки стегнової кістки є рідкісною травмою, із обмеженою кількістю інформації в літературі. Дослідження останніх років базуються на невеликих серіях випадків, де зазначається, що частота переломів у разі вивиху стегна варіює від 7 до 18 %. Переломи головки стегна класифікують за Pipkin. Лікування часто супроводжується значними ускладненнями, і вибір оптимальної методики залишається предметом суперечок. Від тактики лікування залежить як термін, так і функціональний результат. У статті презентовані результати лікування пацієнтів, під час визначення тактики лікування яких використовувалась класифікація Pipkin. Мета. Обґрунтувати застосування класифікації переломів головки стегнової кістки за Pipkin під час вибору лікувально-діагностичної тактики. Методи. Дослідження виконали шляхом оцінювання результатів лікування 44 пацієнтів. Під час визначення тактики лікування використовувалась класифікація за Pipkin. Оцінювання результатів здійснювали за шкалою HHS. Проведено статистичний аналіз результатів — порівняння медіан оцінок для різних груп із використанням U-критерію Манна-Уітні. Результати. Найгірший прогноз для пацієнтів із переломами Pipkin III та Pipkin IV. Оцінка за HHS для осіб з ускладненим перебігом гірша, ніж для пацієнтів з неускладненим. Результати лікування для переломів типу ІІІ за Pipkin статистично значущо менші, ніж для інших типів. Висновки. Переломи Pipkin — рідкісна та важка травма, яка за умов неправильно обраної тактики лікування може призвести до значного порушення функцій кінцівки. Лікування типів І та ІІ за Pipkin включає невідкладне вправлення вивиху й консервативне лікування у випадку задовільного розташування фрагментів або відкриту репозицію з металоостеосинтезом для переломів зі зміщенням; для типів ІІІ та IV у молодих пацієнтів можлива відкрита репозиція й остеосинтез, для осіб старше 60 років чи зі супутніми метаболічними захворюваннями рекомендується розглядати первинне ендопротезування, як варіант вибору.
Using the Pipkin classification in determining the treatment tactics of femoral head fractures
Keywords: перелом головки стегнової кістки; вивих стегна; кульшовий суглоб; остеосинтез; ендопротезування